2004
DOI: 10.1097/01.pcc.0000102386.96434.46
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with early extubation after cardiac surgery in young children

Abstract: Early extubation is possible in many very young children undergoing congenital heart surgery, with a low rate of failed extubation. The model would be improved by prospective validation with larger numbers at multiple institutions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
84
0
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(89 citation statements)
references
References 25 publications
1
84
0
4
Order By: Relevance
“…Indeed, some reports have suggested that OR extubation is successful in cases when the CPB duration is less than 150 minutes or the aortic cross clamp duration is less than 45 minutes. 3,10) Older age is also an important factors associated with the success rate of extubation in the OR. Several reports have stated that the majority of patients older than 6 months were successfully extubated in the OR.…”
Section: Extubation In or After Congenital Heart Surgerymentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, some reports have suggested that OR extubation is successful in cases when the CPB duration is less than 150 minutes or the aortic cross clamp duration is less than 45 minutes. 3,10) Older age is also an important factors associated with the success rate of extubation in the OR. Several reports have stated that the majority of patients older than 6 months were successfully extubated in the OR.…”
Section: Extubation In or After Congenital Heart Surgerymentioning
confidence: 99%
“…[10][11][12] Some reports have suggested that PH be evaluated as mean pulmonary artery pressure (MPAP) divided by mean systemic arterial pressure (MSAP) before and after cardiac surgery. Vida and colleagues 13) reported in 2006 that PH did not seem to be a contra-indication to early extubation after VSD closure, and reported that 65% of their cases (65/100, including those with preoperative MPAP/MSAP < 0.6; extubation rate, 84.6%) were successfully extubated in the OR.…”
Section: Extubation In or After Congenital Heart Surgerymentioning
confidence: 99%
“…The incapacity to sustain spontaneous respiration after extubation has been one of the main factors of failure in extubation [10,[21][22][23][24]. The inexistence of validated extubation protocols adequate for children undergoing correction surgery of congenital heart diseases collaborates with the increase in failure rates during weaning of these patients [18,[21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…Recently it was demonstrated that extubation failure, with consequent re-intubation within 48 hours, is associated with a higher mortality rate compared to successful weaning [17,23,24].…”
Section: Discussionmentioning
confidence: 99%
“…Study of the Neirotti et al (15) showed, as well as our research, that failure to thrive is one of the risk factor of prolonged ventilation [95%CI (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)]. …”
mentioning
confidence: 99%